Strategic competence: issues of task-specific strategies in arithmetic - Ostad, Snorre A. (NOMAD Nordic Studies in Mathematics Education, 1997)
This article focuses on the term strategy and on strategy use in elementary arithmetic. The central theoretical viewpoint in the article includes strategy variability as a fundamental characteristic of mathematical cognition. The theoretical and research base for the acqusition and development of strategic competence is reviewed, and the characteristics of children are discussed from a developmental perspective. Across all areas, the primary focus of this review is to provide a framework for studying the differences, if any, between mathematically normal and mathematically disabled children with regard to the pattern of development that unfolds as the children move up through primary school.